Mudança institucional e emendas ao orçamento da União: avaliando o impacto da EC nº 86 de 2015 (Orçamento Impositivo Flexível) - Oliveira, Dayane Rossy Pereira de (2018)
Institutions are the rules of the game that seek to minimize the costs of social interactions by making behaviors more predictable by defining the actors' strategic calculation of the pursuit of their interests. In order to improve its regulatory function of collective action, some institutions change over time; however, do these institutional changes prove substantive changes in the behavioral pattern of the actors? Looking at the legislative arena, this paper seeks to identify the nuances of the new institutional arrangement in the Brazilian budget process with the implementation of the flexible fiscal budget and possible changes in the pattern of presentation of parliamentary amendments. Using quantitative impact assessment techniques to identify the effect of the new rule on amendments submitted in 2012 and 2016, comparing the before and after the approval of EC nº 86 of 2015.